Age of onset and family history as indicators of polygenic risk for major depression. Issue 5 (2nd February 2017) - Docherty, Anna R.; Edwards, Alexis C.; Yang, Fuzhong; Peterson, Roseann E.; Sawyers, Chelsea; Adkins, Daniel E.; Moore, Ashlee A.; Webb, Bradley T.; Bacanu, Silviu A.; Flint, Jonathan; Kendler, Kenneth S.
Abstract : Background: The extent to which earlier age of onset (AO) is a reflection of increased genetic risk for major depression (MD) is still unknown. Previous biometrical research has provided mixed empirical evidence for the genetic overlap of AO with MD. If AO is demonstrated to be relevant to molecular polygenic risk for MD, incorporation of AO as a phenotype could enhance future genetic studies. Methods: This research estimated the SNP‐based heritability of AO in the China, Oxford and VCU Experimental Research on Genetic Epidemiology (CONVERGE) case‐control sample ( N = 9, 854; MD case, n = 4, 927). Common single nucleotide polymorphism heritability of MD was also examined across both high and low median‐split AO groups, and best linear unbiased predictor (BLUP) scores of polygenic risk, in split‐halves, were used to predict AO. Distributions of genetic risk across early and late AO were compared, and presence of self‐reported family history (FH) of MD was also examined as a predictor of AO. Results: AO was not significantly heritable and polygenic risk derived from the aggregated effects of common genetic variants did not significantly predict AO in any analysis. AO was modestly but significantly lower in cases with a first‐degree genetic FH of MD. Conclusions: Findings indicate that AO is associated with greater self‐reported genetic risk for MD in cases, yet not associated with common variant polygenic risk for MD. Future studies of early MD may benefit more from the examination of important moderating variables such as early life events.